2014
DOI: 10.1590/s0100-06832014000500010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium sources and rates on arabica coffee yield, nutrition, and macronutrient export

Abstract: SUMMARYThe use of potassium (K) rock powder can be an alternative for K supply of crops. Thus, to reduce K fertilizer imports from abroad, possibilities of extracting this nutrient from Brazilian rocks are being studied. The objective was to evaluate the effect of phonolite rock powder (F2) as K source (Ekosil ® ) on the air-dried fruit yield, nutrition and macronutrient export of Arabica coffee. The experiment was carried out on a dystroferric Red Latosol (Typic Haplorthox), in Piraju, São Paulo State, Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 8 publications
3
40
0
7
Order By: Relevance
“…Increased availability of Si favors increased productivity, since Si can act indirectly in photosynthetic and biochemical processes, especially when the plant is subjected to some type of stress [32]. The translocation of silicon from the roots to the aerial part of plants may be related to the increase in photosynthetic capacity, greater resistance to possible damage and reduction in the evapotranspiration process, which, consequently, improves the use of available water in the soil [33]. Calcareous: y = 0,0081x-0,2204 (R 2 =0,96) Calcium silicate: y = 0,0084x-0,3453 (R 2 =0,96) The increase in CO 2 concentration inside leaves promotes the closure of stomata, which may occur in response to a biotic stress [34].…”
Section: Resultsmentioning
confidence: 99%
“…Increased availability of Si favors increased productivity, since Si can act indirectly in photosynthetic and biochemical processes, especially when the plant is subjected to some type of stress [32]. The translocation of silicon from the roots to the aerial part of plants may be related to the increase in photosynthetic capacity, greater resistance to possible damage and reduction in the evapotranspiration process, which, consequently, improves the use of available water in the soil [33]. Calcareous: y = 0,0081x-0,2204 (R 2 =0,96) Calcium silicate: y = 0,0084x-0,3453 (R 2 =0,96) The increase in CO 2 concentration inside leaves promotes the closure of stomata, which may occur in response to a biotic stress [34].…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, unsur K juga berperan dalam reproduksi tanaman kopi, terutama pada hasil dan ukuran biji (Clemente et al, 2013), menentukan kualitas citarasa dengan mengaktifkan enzim polifenol oksidase serta menentukan kandungan kafein dan fenol dalam biji kopi (Gonthier, Witter, Spongberg, & Philpott, 2011;Clemente et al, 2013;Mancuso, Soratto, Crusciol, & Castro, 2014;Clemente, Martinez, Alves, Finger, & Cecon, 2015).…”
Section: Korelasi Ketinggian Tempat Dengan Sifat Kimia Tanahunclassified
“…In the second crop the KCl treatment promoted the highest K absorption (142.5 mg/pot) differing from the other treatments that accumulated about 95.6 to 109.6 mg/pot. Mancuso et al (2014) studied coffee plant nutrition and fertilization efficiency under phonolite rock powder concluded that rock powder can be used as a nutrient source, proving efficient for K supply to coffee.…”
Section: Dry Matter (Dm)mentioning
confidence: 99%